Network traffic prediction based on wavelet transformation and FARIIMA - CHEN Xiao-tian; LIU Jing-xian (Tongxin xuebao)
An advanced network traffic prediction method based on wavelet transformation and FARIMA model was put forward.In the method,the original data was decomposed and reconstructed with Mallat algorithm,then FARIMA model was applied on each branch to predict and integrate the traffic.Simulation is carried out to verify the accuracy of pro-posed algorithm with real network traffic.Compared with the traditional method,the proposed method reduces the pre-diction error.